'Too Big to Fail and Too Big to Succeed': Accounting and Privatisation in the Prison Service of England and Wales. (2nd April 2013) - Mennicken, Andrea
Abstract This paper is concerned with the challenges involved in the transformation of the prison into a performance‐oriented accounting entity. It examines the implication of private sector accounting and consulting expertise in redefining prison values and prison performance, and it discusses the consequences this had for definitions of risk and responsibility. The paper shows how the reforms promoted a systemic decentring of Prison Service accountability. Prison managers and regulators came to be inserted into hierarchies of expertise and credibility shaped by quests for commensuration and auditability. Further, the paper shows how the reform attempts brought about a situation of institutional lock‐in by contributing, as the outgoing HM Chief Inspector of Prisons Anne Owers has put it in 2010, to the creation of an inflated prison system 'too big to fail, and too big to succeed'.